Recent advances of 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN) in photocatalytic transformations - Shang, Tian-Yi; Lu, Ling-Hui; Cao, Zhong; Liu, Yan; He, Wei-Min; Yu, Bing (Chemical communications (Cambridge, England), 2019)
1,2,3,5-Tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN) is a typical donor-acceptor fluorophore, with carbazolyl as an electron donor and dicyanobenzene as an electron acceptor. It has emerged as a powerful organophotocatalyst since 2016. Excellent redox window, good chemical stability and broad applicability make 4CzIPN an attractive metal-free photocatalyst. In this review, the recent advances of the application of 4CzIPN as a photoredox catalyst in the past three years (2016-2018) for various organic reactions are summarized. In this review, the recent advances of the application of 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN) as a photoredox catalyst in the past three years (2016-2018) for various organic reactions are summarized.